PENGARUH KECERDASAN EMOSIONAL, MOTIVASI KERJA DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Rafidi M. Noor; Nurliana .; Umar Nafi; Jonny Hutasoit; Juliawan Samsir Rajagukguk (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Problem of this study how influence of emotional intellegence on performance. How influence of job motivation on performance. How influence of quality work of life on performance. How influence emotional intellegence, job motivation and quality work of life on performance. The purpose of this study to determine and analyze the effect of emotional intellegence on performance. Determine and analyze the effect of job motivation on performance. Determine and analyze the effect of quality work of life on performance. Determine and analyze the effect of emotional intellegence, job motivation and quality work of life on performance. Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate emotional intellegence variable has a positive and significant effect on performance. job motivation variable has a positive and significant effect on performance. quality work of life variable has a positive and significant effect on performance. Emotional intellegence, job motivation and quality work of life variable has a positive and significant effect on performance.